2014
DOI: 10.1158/1055-9965.epi-14-0522
|View full text |Cite
|
Sign up to set email alerts
|

Null Association between Vitamin D and PSA Levels among Black Men in a Vitamin D Supplementation Trial

Abstract: Background Black men exhibit a high prevalence of vitamin D deficiency as well as higher incidence of prostate cancer and higher mortality rates from prostate cancer than Whites. There are few data about the effect of vitamin D3 (cholecalciferol) supplementation on prostate specific antigen (PSA) in healthy Black men. Methods During 3 winters from 2007–2010, 105 Black men (median age, 48.9 years) of Boston, MA were randomized into a 4-arm, double-blind trial for 3 months of placebo, 1000, 2000, or 4000 IU of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…In another study conducted to study the association between VD and PSA levels among black men, it was found that there was no effect on PSA levels, free or total with VD supplementation in men without a cancer diagnosis [22]. However, no correlation was made between patients who had cancer and VD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted to study the association between VD and PSA levels among black men, it was found that there was no effect on PSA levels, free or total with VD supplementation in men without a cancer diagnosis [22]. However, no correlation was made between patients who had cancer and VD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Kristal et al recently reported reduced risk of Gleason 7-10 prostate cancer among AAs in the upper three quintiles of serum 25(OH)D compared to the lower two quintiles in the Selenium and Vitamin E Cancer Prevention Trial [22]. In a recent randomized, placebo-controlled clinical trial, varying doses of vitamin D supplementation had no effect on PSA levels in healthy AA men without prostate cancer [50]. The current study results, along with these recent reports underscore the need for more research on vitamin D and prostate health among AAs who have been underrepresented in previous research studies.…”
Section: Discussionmentioning
confidence: 99%
“…A neighboring unbleached cell served as a control for focus drift and photobleaching during image acquisition. Normalization was done to the pre-bleach data point (39). At least 10 cells were collected per treatment condition.…”
Section: Live Cell Imaging Using Flip Microscopymentioning
confidence: 99%